2022
DOI: 10.1371/journal.pone.0279159
|View full text |Cite
|
Sign up to set email alerts
|

The moderation role of board independence change in the relationship between board characteristics, related party transactions, and financial performance

Abstract: The present study examines the moderation effect of board independence change on the relationship between board characteristics, related party transactions and financial performance of Indian listed banks over 10 years from 2010 to 2019. While board size, independence, diligence, and remuneration were taken to represent board characteristics, all key personnel and subsidiaries’ transactions were considered measures for related party transactions. On the other hand, the financial performance of banks was measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 126 publications
(232 reference statements)
0
2
0
Order By: Relevance
“…Several studies have established an evidence on the association between ESG disclosures and CG mechanisms; board size [ 23 , 25 , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] ]. Most of the existing studies on this topic have found evidence of a positive and significant correlation between board size and both ED and sustainability performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies have established an evidence on the association between ESG disclosures and CG mechanisms; board size [ 23 , 25 , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] ]. Most of the existing studies on this topic have found evidence of a positive and significant correlation between board size and both ED and sustainability performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study showed an average tunnelling value of 0.038. Meanwhile, research in India conducted by [4] regarding the moderation effect of independent boards in the relationship between related party transactions and banks' financial performance showed an average related party transactions value of 0.03. Furthermore, research in Hong Kong conducted by [57] on Capital-Market Liberalization and Controlling Shareholders' Tunneling showed an average tunnelling value of 0.0161.…”
Section: Descriptive Statisticsmentioning
confidence: 99%
“…This agrees with prior works. For example, Almaqtari et al (2022) indicate that board independence plays a crucial role in explaining disparities in the quality of environmental performance. Similarly, Rupley et al (2012) conclude that the readiness of a company to provide transparent environmental performance that is accessible to a wide range of stakeholders is influenced by board independence.…”
Section: Correlation Analysismentioning
confidence: 99%